Required biological time for lung maturation and duration of invasive ventilation: a Korean cohort study of very low birth weight infants - Jo, Heui Seung; Lim, Myoung Nam; Cho, Sung-Il (Frontiers in Pediatrics, 2023)
Background We investigated the duration of invasive ventilation among very low birth weight (VLBW) infants to evaluate the current minimum time required for lung maturation to breathe without ventilator assistance after preterm birth. Methods A total of 14,658 VLBW infants born at ≤32+6 weeks between 2013 and 2020 were enrolled. Clinical data were collected from the Korean Neonatal Network, a national prospective cohort registry of VLBW infants from 70 neonatal intensive care units. Differences in the duration of invasive ventilation according to gestational age and birth weight were investigated. Recent trends and changes in assisted ventilation duration and associated perinatal factors between 2017–20 and 2013–16 were compared. Risk factors related to the duration of assisted ventilation were also identified. Results The overall duration of invasive ventilation was 16.3 days and the estimated minimum time required corresponded to 30+4 weeks of gestation. The median duration of invasive ventilation was 28.0, 13.0, 3.0, and 1.0 days at <26, 26–27, 28–29, and 30–32 weeks of gestation, respectively. In each gestational age group, the estimated minimum weaning points from the assisted ventilator were 29+5, 30+2, 30+2, and 31+5 weeks of gestation. The duration of non-invasive ventilation (17.9 vs. 22.5 days) and the incidence of bronchopulmonary dysplasia (28.1% vs. 31.9%) increased in 2017–20 (n = 7,221) than in 2013–16 (n = 7,437). In contrast, the duration of invasive ventilation and overall survival rate did not change during the periods 2017–20 and 2013–16. Surfactant treatment and air leaks were associated with increased duration of invasive ventilation (inverse hazard ratio 1.50, 95% CI, 1.04–2.15; inverse hazard ratio 1.62, 95% CI, 1.29–2.04). We expressed the incidence proportion of ventilator weaning according to the invasive ventilation duration using Kaplan–Meier survival curves. The slope of the curve slowly decreased as gestational age and birth weight were low and risk factors were present. Conclusions This population-based data on invasive ventilation duration among VLBW infants suggest the present limitation of postnatal lung maturation under specific perinatal conditions after preterm birth. Furthermore, this study provides detailed references for designing and/or assessing earlier ventilator weaning protocols and lung protection strategies by comparing populations or neonatal networks.